A robust auto-synchronizer for synchronverter. (March 2022) - Naeem, Muhammad; Ashraf, Muhammad; Khan, Umer Amir
Abstract: The increasing deployment of inertia-less power electronic converters poses serious concerns on power system frequency stability. Synchronverter has certain features like virtual inertia, damping and voltage regulation embedded in its controller. Therefore, it can support system frequency and voltage in power grids. Like synchronous generator, it has ability to remain synchronized with the grid. However, it requires a synchronizer to track grid phase and frequency as reference before grid connection. This paper proposes a robust PLL-less Auto-synchronizer for synchronverter that allows it to synchronize with grid without interrupting its output power. The proposed synchronizer ensures fast synchronization independent of adverse grid conditions. Moreover, it has less computational burden on controller. The robustness of proposed synchronizer is validated by simulations. Results have shown that the proposed synchronizer is a fast and promising solution of synchronization of synchronverter with grid independent of certain grid conditions. Graphical abstract: Highlights: Synchronverter mimics synchronous generator in stand-alone and grid-connected mode. PLL-less synchronization of synchronverter is better and reliable. Synchronization methods of synchronous generator are applicable on synchronverter. Fast and reliable grid-synchronization is achieved under adverse grid conditions.